MODEL KELEMBAGAAN KAWASAN METROPOLITAN DI INDONESIA - warseno, warseno (Jurnal Sains dan Teknologi Indonesia, 2011)
Metropolitan area in Indonesia is growing as fast as population’s growth andeconomic activities that go along with agglomeration process in all aspects inexisting big cities such as Jakarta, Surabaya, Medan, Bandung, Makassar andothers. It is pity that trend of functional urban growth is not anticipated and early prepared with setting up the metropolitan institution that optimally and effectively manage the development and growth of the big cities in Indonesia. To anticipate, it is needed model of the metropolitan institution appropriate with valid law and regulations.